Efektivitas Penerapan Metode Imla’ Mandzur terhadap Kelancaran Hafalan Al-Qur'an di SDIT Al Madaniy Lubuk Basung - Zahra Tullatifah; Al Baihaqi Anas (Lembaga Yasin AlSys, 2026)
Fluency in Qur’an memorization is an important indicator of the success of tahfiz programs in Islamic educational institutions; however, some students still experience difficulties in achieving and maintaining memorization fluency according to the established targets. This study aims to analyze the effectiveness of implementing the Imla’ Mandzur method on the Qur’an memorization fluency of Grade VI students at SDIT Al Madaniy Lubuk Basung. This study used a quantitative approach with a quasi-experimental pretest–posttest control group design. The research participants consisted of 53 students, comprising 27 students in the experimental group and 26 students in the control group, selected using random sampling. Data were collected using pretest and posttest assessments as well as documentation, then analyzed through normality testing, N-Gain Score calculation, and the Independent Samples t-test with the assistance of IBM SPSS Statistics version 26. The results showed that the average posttest score of the experimental group was 84.22, higher than that of the control group, which was 76.46. The N-Gain Score results showed an increase of 60.2819% in the experimental group, categorized as moderately effective, whereas the control group obtained an increase of 41.9864%, categorized as ineffective. The Independent Samples t-test results showed a significance value of 0.007 (p < 0.05), indicating a significant difference between the two groups. The conclusion of this study affirms that the Imla’ Mandzur method is effective in improving students’ Qur’an memorization fluency. These findings contribute to the development of tahfiz learning based on integrated listening, seeing, writing, and memorizing activities, and provide practical implications for Islamic educational institutions in selecting more effective learning strategies to improve the quality of Qur’an memorization.